Mercy Falls [videorecording (Blu-Ray)] - Hendrick, Ryan; Grasska, Melia; Lyle, Lauren, 1992-; McKeown, Nicolette; Watterson, James; Kirk, Layla; Rising, Joe (Magic Monkey Films, 2023)
A group of friends set off into the Scottish Highlands in search of a long lost cabin. Once far from civilization, an unforeseen tragedy befalls the group and one bad decision leads to suspicion, betrayal and murder.